Mediation effect of environmental performance in the relationship between green supply chain management practices, institutional pressures, and financial performance - Ma, Xin; Akhtar, Raheel; Akhtar, Adeel; Hashim, Raema Abdullah; Sibt-e-Ali, Muhammad (Frontiers in Environmental Science, 2022)
Pakistan is an agricultural country that uses a huge number of pesticide chemicals and is confronting environmental and economic issues. Firms need to comprehend the integration of green supply chain management (GSCM) practices in their supply chain. The current study intends to analyze the mediation effect of environmental performance (ENP) in the relationship between GSCM practices, institutional pressures (IP), and financial performance (FNP). Therefore, GSCM-IP-ENP-FNP model was developed with the help of an extensive literature review and then proved with the help of data collected from pesticide chemical firms working in Pakistan. Data were collected through a questionnaire from 500 senior-level managers of the pesticide firms of Pakistan. However, 468 responses were retained for analysis keeping in view the limitations of the current study. SPSS version 22 and SmartPLS 3.0 were used for data analysis. Results of the study indicated strong relationships among all variables. It was also concluded that GSCM practices, IP, and ENP have a positive and statistically significant relationship with a firm’s FNP. This study is an important contribution to theory and practice. The study is unique and has significant contributions because it developed and proved the GSCM-IP-ENP-FNP model. The model helped to prove the mediation effect of ENP in the relationship between GSCM practices, IP, and FNP in the pesticide sector of Pakistan, which would be highly beneficial for the managers of pesticide firms as well as for the government to understand the importance of GSCM practices for improving the ENP as well as the FNP of pesticide firms in Pakistan as well as worldwide, especially in developing countries. This study recommends that the management of firms should implement GSCM practices to protect the environment. Government, consumers, and other institutions should exert pressure and the government should provide subsidies, if necessary, to the firms for successful implementation of GSCM practices. Furthermore, it is recommended to conduct further studies in other countries by using the mixed methodology in the pesticide sector as well as in other sectors of the economy to increase the generalizability of the current study.